Learning old age and learning in old age: an individual perspective - Semków, Jerzy (Old Age in the Stream of Life: Reflections on Old Age. Volume 2, 2019)
Learning old age has an essentially individual character since it is dependent on many different factors. The first one is the age of a person which, as I argue by referring to personal experiences, has a huge influence on our attitude towards seniors – from the acceptance and respect for old age to its disavowal as a mark of a declining and decrepit lifeform. The second factor, nonetheless also important, is the experience of living in a multigenerational family in which the eldest members are deemed significant and entertaining respect. Another factor that shapes our perception of seniors is the level of environmental and widely societal awareness of the significance of aging processes and of their inevitability in the life of every human being. In that matter, we are still burdened with a feeling of inferiority as those who were bound to live on until the age of seventy, eighty, and ninety. Deeply ingrained, and stemming from a bad tradition, a belief that leads one to commonly associate old age as the one “on which God had failed” is very slowly being eliminated from the collective consciousness. The process is enhanced by a new opening of the last phase of life which as a result of constant lengthening acquires a new dimension, followed by a new meaning. Numerous examples of old people who take care of their psychophysical condition and their social and spiritual development are gradually retrieving old age to its rightful place in the human lifespan. In this process of change, a leading role seems to be played by a person’s spiritual development whose important component is spiritual practice wherein and thanks to which old age acquires the status of life’s period not worse than its previous stages.